Type-II defects in the super-Liouville theory - Aguirre, A. R.; Burdik, C.; Navratil, O.; Posta, S. (Iop Publishing Ltd, 2013)
The introduction of type-II defects is discussed under the Lagrangian formalism and Lax representation for the N = 1 super-Liouville model. We derive a new kind of super-Backlund transformation for the model and show explicitly the conservation of the modified energy and momentum, as well as supercharge.